2022
DOI: 10.3390/app121910040
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS Analysis of A Helichrysum italicum Hydrosol: Sensitivity, Repeatability and Reliability of Solvent Extraction versus Direct Hydrosol Analysis

Abstract: Hydrosols have been increasingly used in the food industries as drinks and as ingredients for seasoning and flavoring. Research has shown they have antimicrobial, antioxidative and anti-inflammatory effects and therefore have potential as food preservative agents and sanitizing agents for tools used in the food industry. The composition analysis of hydrosols is commonly conducted using extraction with organic solvents. However, some hydrophilic compounds are lost with this procedure, leading to issues in ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Other major compounds in this report were 2,2dimethylnon-5-en-3-one (8.8-13.0 %), 3-octanone (8.0-12.3 %) and α-terpineol (7.6-9.1 %), while in the observed Croatian populations 2,2-dimethylnon-5-en-3-one (14.69-18.40 %) and αterpineol (11.8-19.55 %) were listed as the major compounds. On the other hand, our results do not agree with those of Kokalj Ladan and Kočevar Glavač [12] who reported 1,8-cineole (34.7 %), terpinen-4-ol (14.4 %), α-terpineol (14.0 %), and linalool (10.4 %) as major components of immortelle hydrosol. Furthermore, some reports dealing with the chemical composition of immortelle hydrosol, indicated that α-terpineol is reported as the most dominant compound (15.6-30.5 %) [9][10][11] whereas this compound was not detected in our hydrosol sample.…”
Section: Chloroform Casecontrasting
confidence: 99%
See 4 more Smart Citations
“…Other major compounds in this report were 2,2dimethylnon-5-en-3-one (8.8-13.0 %), 3-octanone (8.0-12.3 %) and α-terpineol (7.6-9.1 %), while in the observed Croatian populations 2,2-dimethylnon-5-en-3-one (14.69-18.40 %) and αterpineol (11.8-19.55 %) were listed as the major compounds. On the other hand, our results do not agree with those of Kokalj Ladan and Kočevar Glavač [12] who reported 1,8-cineole (34.7 %), terpinen-4-ol (14.4 %), α-terpineol (14.0 %), and linalool (10.4 %) as major components of immortelle hydrosol. Furthermore, some reports dealing with the chemical composition of immortelle hydrosol, indicated that α-terpineol is reported as the most dominant compound (15.6-30.5 %) [9][10][11] whereas this compound was not detected in our hydrosol sample.…”
Section: Chloroform Casecontrasting
confidence: 99%
“…Moreover, the ratios between the compounds detected in the hydrosol may differ from their original chemical composition due to different partition coefficients between water and organic solvent for each compound present in the hydrosol. [12]…”
Section: Total Volatile Organic Compoundsmentioning
confidence: 99%
See 3 more Smart Citations